The activity of adenosine monophosphate-activated protein kinase in lymphocytes under the action of hypoglycemic drugs - Sokolova, L.K.; Pushkarev, V.M.; Belchina, Yu.B.; Pushkarev, V.V.; Tronko, N.D. (Reports of the National Academy of Sciences of Ukraine, 2017)
We have studied the activity of adenosine monophosphate-activated protein kinase (AMPK), which controls the energy balance in a cell, after the treatment of patients with diabetes with hypoglycemic agents. It is shown for the first time that metformin increases the AMPK activity in lymphocytes. Dapagliflozin, an inhibitor of sodium-dependent glucose transporter, also increases the protein kinase activity in blood cells and exerts an additive effect to metformin. The mechanisms of impact of the antidiabetic drugs on the level of AMPK activity are discussed.